146 The impact of a new integrated supportive care service for patients with interstitial lung disease. (14th March 2023) - Douglas, Claire; Rowe, Fiona; Bowers, Sarah; Hammond, Richard; Goudie, Andrew
Abstract : Background: Interstitial Lung Disease (ILD) can have a prognosis of 2–5 yrs with symptom burden comparable to lung cancer. Advance Care Planning (ACP) is poor and dying is often unrecognised. Funding was obtained for a Palliative Care consultant and ILD nurse to provide a fortnightly clinic, alongside the ILD consultant. The aim of the service: to improve symptom control and ACP, alongside routine respiratory care. Methods: Outcomes were reviewed for the first 50 patients attending clinic within 6 months of the service commencing. Patients were selected by the ILD consultant. Symptoms were assessed using the Integrated Palliative Outcome Scale (IPOS). ACP conversations were documented electronically to the GP with a request to update the Scottish Key Information Summary (KIS). The IPOS scores and information on the KIS were compared from first to last consultation. Results: First and last IPOS scores were available for 33/50 (66%) patients. Symptom burden was high: breathlessness (90%), Fatigue (80%), Anxiety (78%), Depression (60%), Pain (30%). Cough (20%) and insomnia (15%) were mentioned (not routinely measured by IPOS). Most symptoms improved; pain (p=0.035) and anxiety (0.040) reduced significantly. Pre-service 11/50 (22%) patients had ACP documented on KIS with DNA CPR documented in 4/50 (8%). Post-service, 31/50 (62%) had ACP documented (p=0.003). ACP was uploaded to the KIS in 25/31 (81%). DNACPR discussions were documented for 19/50 (38%) (p=0.008) with 17/19 (89%) of these uploaded to the KIS. Preferred place of death (PPD) was documented for 29/50 (58%) patients. 19/29 (66%) stated a PPD for home, 10/29 (33%) for hospital. 11/50 (22%) patients died within the 6 months. Of these, 7/11 (64%) had documented PPD for home. This was achieved in 6/7 (86%). Conclusion: The integrated ILD Supportive Care service improves symptom burden for patients, improves ACP and may reduce unwanted hospital admissions at end of life.